2013
DOI: 10.1063/1.4847875
|View full text |Cite
|
Sign up to set email alerts
|

A revisitation of the Förster energy transfer near a metallic spherical nanoparticle: (1) Efficiency enhancement or reduction? (2) The control of the Förster radius of the unbounded medium. (3) The impact of the local density of states

Abstract: The central motivation of this theoretical revisitation comes from the fact that some experimental works about Förster energy transfer report improvement of the Förster efficiency when the donor-acceptor molecular pair is in the vicinity of a metallic particle, while others found efficiency deterioration. In the presence of a nanoscale metallic sphere, we calculate contour plots of the Förster energy transfer rate KF and the Förster efficiency η as a function of the acceptor position rA for a fixed donor posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 61 publications
1
65
0
Order By: Relevance
“…In regard to Förster energy transfer, which is crucial for energy transfer upconversion (ETU) -the most significant upconversion process for lanthanide-doped upconverter materials -there is an ongoing discussion in the literature whether or not the rate of Förster energy transfer is influenced by the local density of photon states [40][41][42][43][44][45][46][47]. Following the argumentation by Dood et al [45] and the experimental findings by Rabouw et al [46], no modification of the energy transfer rate due to a locally modified density of photon states due to the presence of the metal nanoparticle was implemented into the model used for the investigations presented in this paper.…”
Section: Radiative Couplingmentioning
confidence: 99%
“…In regard to Förster energy transfer, which is crucial for energy transfer upconversion (ETU) -the most significant upconversion process for lanthanide-doped upconverter materials -there is an ongoing discussion in the literature whether or not the rate of Förster energy transfer is influenced by the local density of photon states [40][41][42][43][44][45][46][47]. Following the argumentation by Dood et al [45] and the experimental findings by Rabouw et al [46], no modification of the energy transfer rate due to a locally modified density of photon states due to the presence of the metal nanoparticle was implemented into the model used for the investigations presented in this paper.…”
Section: Radiative Couplingmentioning
confidence: 99%
“…There have been numerous experimental [67][68][69][70][71][72][73][74][75][76][77] and theoretical [78][79][80][81][82][83] studies of the ET process in donor-acceptor pairs. The studies reported increases in the ET rate, range, and efficiency for various NP materials, sizes, and geometries.…”
Section: B Energy Transfer Ratesmentioning
confidence: 99%
“…The energy transfer process has also been studied more recently in Ref. 83 for Ag spheres of 5 nm and 25 nm diameter. These are just some of the examples of studies reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, since an emitter can be efficiently coupled to a surface plasmon, it has been proposed to use plasmon to couple two emitters for applications such as long range resonant energy transfer (above 10 nm) [93,94,95,96,97] or qubits entanglement [98,99]. In the following, we discuss the plasmonic Purcell factor for typical configurations.…”
Section: Dipole-dipole Couplingmentioning
confidence: 99%